PERALIHAN TRANSFORMASI MEDIA PEMBELAJARAN DARI LURING KE DARING DALAM PENDIDIKAN AGAMA ISLAM - Unik Hanifah Salsabila; Antika Melania; Alfia Miftakhul Jannah; Irada Haira Arni; Bunga Fatwa (Universitas Muhammadiyah Tapanuli Selatan, 2020)
The world of education is feeling a tremendous impact with the Covid-19 pandemic. In the implementation, teaching and learning activities are completely diverted using online media, because it has been recommended by the Government and is expected to help in the learning process, because the learning process of teaching should not stop because of the pandemic. According to the hadeeth of the prophet